SOSIALISASI PERATURAN PERPAJAKAN DAN KINERJA ACCOUNT REPRESENTATIVE KAITAN DENGAN KEPATUHAN WAJIB PAJAK - Farikha, Intan; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to explain implementation of tax socialization and Account Representative performance in supporting the taxpayers in fulfilling their tax obligation at Kantor Pelayanan Pajak Pratama Sidoarjo Barat. Taxpayers compliance can be identified from signing up, submitting tax returns (SPT), making calculation and paying tax payable. This research is a qualitative research which hase been case study and field study by using structured interview with seven tax officers i.e.: Head of Service Section, Chief of Extensification Section, Chief of Supervision and Consulting Section, Head of Sub General Division and three people of Account Representative and ten people of effective Taxpayers who are registered at Kantor Pelayanan Pajak Pratama Sidoarjo Barat which has become the focus of this research.The result of this indicate the level of submitting tax return (SPT) increasing every year proving that the taxpayer is increasing awareness that the role of Account Representative as a supervisor, supervising and consulting in tax laws provide socialization is good.Keywords: Tax Rules Socialization, Account Representative Performance, Taxpayers Compliance.